Profiling Initial Thrombin Generation in Cardiovascular Disease using a High Sensitivity Coagulation Assay - Fujiyama, Akira; Arima, Yuichiro; Inoue, Rina; Kuyama, Naoto; Yamamoto, Masahiro; Hirakawa, Kyoko; Ishii, Masanobu; Hanatani, Shinsuke; Matsuzawa, Yasushi; Yamamoto, Eiichiro; Izumiya, Yasuhiro; Komatsu, Mariko; Kamikubo, Yuichi; Tsujita, Kenichi (Thrombosis and Haemostasis)
Background: Initial thrombin (FIIa) generation is a critical trigger for the amplification and propagation phases of coagulation, driven by two distinct pathways: the tissue factor (TF) and the FVIIIa/IXa pathways. However, the clinical utility of measuring initial thrombin generation (ITG) as a marker of thrombogenicity or as a tool to monitor the efficacy of oral anti-FXa therapy remains uncertain. Methods: ITG driven by TF- and the FVIIIa/IXa complex was first measured in plasma samples from healthy adults (n = 40). This was followed by an analysis of ITG profiles in 771 consecutive patients with cardiovascular diseases to evaluate the effects of anticoagulant therapy and clinical characteristics. Results: Of the 771 patients studied, 169 were receiving DOACs. DOAC treatment significantly suppressed thrombin generation via both TF- and FVIIIa/IXa pathways. Receiver operating characteristic (ROC) analysis confirmed the strong discriminatory power of both pathways for detecting DOAC use (FVIIIa/IXa: AUC 0.863, 95% CI: 0.825–0.900; TF: AUC 0.887, 95% CI: 0.856–0.917; both p < 0.0001). Among patients not on anticoagulants, logistic regression revealed that dialysis was associated with reduced thrombin generation through both pathways. Furthermore, chronic kidney disease and active cancer were specifically associated with diminished TF-driven thrombin generation. Conclusions: ITG driven by TF- and FVIIIa/IXa pathways represent promising biomarkers for evaluating anticoagulant efficacy. Moreover, the distinct influence of pathological conditions on each pathway underscores the need to account for specific disease contexts when assessing coagulation potential.